PENERAPAN METODE PRFOILE MATCHING DALAM PENGAMBILAN KEPUTUSAN PEMILIHAN PENERIMA BANTUAN RUMAH SEHAT - Wati, Nursetia; Mooduto, Sriwahyunangsi (JURNAL TEKNIK INFORMATIKA, 2021)
A decision supporter that can assist the village government in determining recipients of healthy housing assistance. The parameters used consisted of house roof, house ceiling, walls, floors, land status, sanitation, occupation, age of marriage and number of dependents. The method used in this research is Profile Matching. The final result produced in this study is to present the prospective recipients of healthy housing assistance who received the highest ranking value, from the highest ranking data obtained seven prospective recipients of healthy housing assistance with the acquisition value of 4.84.